ANALISIS TINGKAT PENGETAHUAN PETANI TENTANG PEMUPUKAN DAN PRODUKTIVITAS PADI SAWAH DI KELURAHAN RANOMEETO KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Sitti Ashara; Dasmin Sidu; Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The inadequate understanding amongst farmers regarding balanced fertilisation, particularly with regard to fertiliser types, application rates and timing, has resulted in suboptimal rice cultivation practices in Ranomeeto Village, leading to low productivity in comparison to the potential yields that could be achieved. The objective of this study is to analyse the knowledge possessed by farmers in Ranomeeto Village, Ranomeeto Subdistrict, South Konawe Regency, with regard to fertilisation and rice productivity. The present study employs a quantitative approach. The study population consists of all farmers engaged in irrigated rice farming in Ranomeeto Village, totalling 106 farmers. The sampling method employed was a form of probability sampling, specifically simple random sampling. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in a sample of 51 irrigated rice farmers. The data collection techniques employed in this study encompassed in-depth interviews, surveys, and documentation. The study's variables encompassed the farmers' knowledge levels concerning fertilisation and the productivity of irrigated rice. The subsequent data analysis employed quantitative descriptive analysis, utilising percentage and productivity formulas corresponding to the variables under study. The findings of the study suggest that farmers in Ranomeeto Village have relatively good knowledge levels regarding rice field fertilization, particularly with regard to the utilisation of urea and Phonska fertilizers, as evident in their recall, comprehension, and application skills. However, their analytical, evaluative, and creative skills remain deficient. It is evident that farmers' comprehension of manure utilisation is found to be inadequate at all levels of expertise. Rice productivity in Ranomeeto Village reached 4.7 tons/ha, which is higher than the district and sub-district levels. However, this productivity figure is still not optimal when compared to the productivity potential of the high-yielding Inpari 32 variety. Therefore, improved extension services and the application of more appropriate and balanced fertilization techniques are required.